Survey Of Image Processing Techniques In Medical Image Analysis And Identification - et. al., Selin vironicka A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A detailed analysis of the medical image is an important step in radiation preparation. The image processing is mostly radiological, medical and treatment planning techniques. Image processing is a major part of real-time applications in the modern world. This technique of image processing enables better digital image solutions to be found. The image processing tools have different techniques, most of them including abstractions of the compressed image data in order to reduce the quality of the image, noise-free image processors and saving space. This paper helps users to investigate the different technologies used by medical imaging to diagnose human body detection as well as to develop new techniques to improve the detection accuracy. This paper also presents technologies that apply image processing techniques to the classification of medical images with advantages and disadvantages.